Sub Clinical Hypothyroidism is Associated with Low Grade Inflammation High Plasma Fibrinogen Levels and High Atherothrombotic Potentiality - Kamal, Abu Hena Mostafa; Kabir, Asma; Chowdhury, SM Muizzul Akhar (Journal of Chittagong Medical College Teachers' Association, 2011)
Key words: Hypothyroidism; C-reactive protein; plasma fibrinogen; cardiovascular disease; lipids DOI: 10.3329/jcmcta.v21i2.7730 Journal of Chittagong Medical College Teachers' Association 2010: 21(2):11-15